Effect of Diabetes Mellitus on the Sensorineural Hearing Loss - Aslam, Uroosa; Ejaz, Rabea; Qamer, Samina; Ambreen, Fareeha; Maqsood, Iram (Indus Journal of Bioscience Research, 2025)
Diabetes mellitus (DM) is a chronic, long-term disease causing consistently elevated blood glucose levels due to inadequate insulin production, targeting people of all ages, genders, and geographical areas worldwide. DM raises the incidence of sensorineural hearing loss (SNHL) in adult population. The present cross-sectional and observational study is focused on the prevalence of DM, its impact on hearing ability, complications, and risk factors that contribute to the chronic condition of DM across the population of city Rawalakot, Azad Jamu & Kashmir. The status of DM and hearing ability were evaluated using a combination of HbA1c and pure tone audiometry (PTA) test, respectively, while data on the risk factors and complications were collected via questionnaire. The results of the present study suggested that out of 200 individuals, 60% were diabetic and 40% were non-diabetic. The results of the present study suggested a significant increasing trend in DM prevalence with age. Females have a higher prevalence (55%) compared to males (45%). The present study suggested a strong correlation between SNHL & diabetes (P < 0.05). Severe hearing loss is prevalent in both genders, with females having a higher prevalence rate (56%) compared to males (51%). Prolonged diabetic duration (>9 years) and poor glycemic control (HbA1c>8) adversely affected the hearing ability. DM is strongly linked (P> 0.05) to various health related complications, including retinopathy, nephropathy and urinary tract infections. Moreover, hypertension, anxiety, stress, and a sedentary lifestyle are significant risk factors for DM. Early diagnosis, preventive interventions, time-to-time blood glucose monitoring, and regular hearing assessment are needed for preventing and managing DM and SNHL.